Independence of the Police of the Republic of Indonesia in Realizing the Supremacy of Law: Kemandirian Kepolisian Republik Indonesia dalam Mewujudkan Supremasi Hukum - Dwi Edi Wibowo; Liana Endah Susanti (Indonesian Journal of Police Studies, 2021)
This paper analyzes the position of the police institution and the independence of the police institution in Indonesia in realizing the supremacy and justice of the law.